Measurement of IT Governance Capabilities Using COBIT 2019 in the Indonesian Business Sector - Cuatanto, Ricardo; Sutomo, Rudi (The Indonesian Journal of Computer Science, 2023)
The Indonesian business sector uses information technology to support private, business, and governmental decision-making. However, there are problems with IT implementation, such as a weak Business Continuity Plan, a lack of change testing procedures, and insufficient project review activities. Utilising the COBIT performance model based on COBIT 2019, this study seeks to evaluate the IT governance of the Indonesian business sector. The chosen domains are BAI05 (Managed Organizational Change), BAI06 (Managed IT Changes), and BAI07 (Managed IT Change Acceptance and Transitioning). According to the results, BAI05 scored level 2 (90.6%), BAI06 scored level 2 (80.3%), and BAI07 scored level 2 (87%) respectively. Level 3 (78%) is where BAI07 falls short and needs to be improved. Following a set timeline, recommendations will be implemented once they have been approved by SM Innovation & Digital Transformation and Manager Innovation & IT Project Management in the Indonesian Business Sector.